O financiamento da previdência social como instrumento de proteção ao meio ambiente do trabalho - Guimarães, Julia Henriques (2014)
The purpose of this paper is to discuss the extent to which the current tools for funding the social security may interfere with the prevention in the work environment by means of the extra-taxation attribute. Based on the study of the development of the fundamental rights and, in particular the social rights, this paper contextualizes where the social security and the guarantee of a healthy work environment are inserted. Following, by tracing the development of the social security in Brazil and in the world, it seeks defining how the social risk was formerly handled until the achievement of the tools used nowadays applying the concept of Social Security System provided for in the 1988 Federal Constitution. After that, the form of funding of the social security system is extensively analyzed for the social contributions, and specifically the social security contributions, to be categorized and for the legal system applicable to them to be defined. Subsequently, the funding tools used in the social security system, aimed at funding the benefits paid in the event of occupational diseases and accidents, are individually analyzed. Such list of tools comprises the Occupational Accident Insurance [Seguro contra Acidentes do Trabalho SAT], the additional SAT amount and the Accident Prevention Factor [Fator Acidentário de Prevenção FAP]. The actions for payment of reimbursement to the public treasury for social security expenses arising out of wrongdoings are also analyzed. Thus, we demonstrate that the development of the social security is closely related to the attribution of the extra-taxation characteristic to the social security contributions, given that such characteristic allows the use of the contributions as a tool to promote the protection of the work environment, uncovering the new posture the social security assumed to minimize social risks and, consequently, to stand up for the social rights